Factors associated with delayed neonatal bathing in Afghanistan: insights from the 2022–2023 multiple indicator cluster survey - Stanikzai, Muhammad Haroon; Tawfiq, Essa; Jafari, Massoma; Ezadi, Zainab; Wasiq, Abdul Wahed; Dadras, Omid (Biomed Central, 2026)
Objectives
Delayed neonatal bathing, defined as postponing the first bath until at least 24 h after birth, is a key component of essential newborn care that helps maintain thermal stability and reduces the risk of hypothermia and infection. This study estimates the national prevalence of delayed neonatal bathing and identifies its determinants in Afghanistan. This study analyzed data from the Afghanistan Multiple Indicator Cluster Survey (MICS) 2022–2023. We fitted multivariable binary logistic regression models to determine factors associated with delayed neonatal bathing.
Results
Out of 7,702 women, 68.6% reported delayed neonatal bathing. After adjustment, the odds of delayed bathing were higher among women whose household head completed primary education (AOR 1.38; 95% CI: 1.10–1.73), those delivering in health facilities (AOR 1.57; 95% CI: 1.29–1.91), and women attending 1–3 antenatal care (ANC) visits (AOR 1.29; 95% CI: 1.08–1.53) or 4–7 ANC visits (AOR 1.40; 95%CI: 1.14–1.72) or ≥ 8 ANC visits (AOR 2.05; 95% CI: 1.46–2.87). Conversely, women in the richest wealth quintile were less likely to delay bathing (AOR 0.69; 95% CI: 0.51–0.94). Tailored interventions that leverage antenatal contacts and facility-based care may further improve the adoption of optimal newborn bathing practices in Afghanistan.